Education and Mental Health: Self-Care Proposals from a Teacher's Perspective - Rejido Sánchez, Giselle (2024)
The objective of this study is to evaluate the discursive register of teachers in the II region of Antofagasta, Chile, regarding teacher self-care, to contribute to the design of effective strategies that promote mental health and well-being in educational institutions. The study used a phenomenological-hermeneutic research design, under a qualitative methodological approach that included the participation of 420 teachers from the regional school system. The information collection instruments included open-ended surveys and documentary records. The discursive analysis was conducted through the categorization and coding of the information obtained, using inductive logic. Regarding the results, the teachers' discourse leans more towards recreation than self-care, omitting practices that contribute to comprehensive care. In the emotional realm, there is a noticeable absence of practices that strengthen personal reflection, self-perception, and emotional management. In the social realm, the importance of cultivating social relationships is emphasized, while also strengthening the deep connection with one's inner self. It is crucial to point out that a significant number revealed not engaging in self-care activities or not knowing how to identify them. Additionally, none of the educational units have a systematization of practices that promote the preventive care of their mental health. As for the documentary analysis, the proposals lean towards the emotional dimension as the central axis supporting mental health care. In conclusion, it is noted that educational units need to design, implement, and systematize strategies to address, raise awareness, and support education professionals. Finally, the study projects the expansion to new lines of research aimed at analyzing the feasibility of the proposals with a territorial focus, evaluating and adjusting the implementation of work plans centered on the mental health care of the participant group and their impact on promoting self-care for the continuous improvement of conducive educational environments.